Hemodynamic Response to Treatment and Outcomes in Pulmonary Hypertension Associated With Interstitial Lung Disease Versus Pulmonary Arterial Hypertension in Systemic Sclerosis: Data From a Study Identifying Prognostic Factors in Pulmonary Hypertension Associated With Interstitial Lung Disease. Issue 2 (29th December 2020) - Chauvelot, Louis; Gamondes, Delphine; Berthiller, Julien; Nieves, Ana; Renard, Sébastien; Catella‐Chatron, Judith; Ahmad, Kais; Bertoletti, Laurent; Camara, Boubou; Gomez, Emmanuel; Launay, David; Montani, David; et al.
Abstract : Objective: Patients with systemic sclerosis and both pulmonary hypertension and interstitial lung disease (SSc–PH‐ILD) generally carry a worse prognosis than patients with SSc and pulmonary arterial hypertension (SSc‐PAH) without ILD. There is no evidence of the efficacy of PAH therapies in SSc–PH‐ILD. We undertook this study to compare survival of and response to treatment in patients with SSc–PH‐ILD and those with SSc‐PAH. Methods: We analyzed 128 patients (66 with SSc–PH‐ILD and 62 with SSc‐PAH) from 15 centers, in whom PH was diagnosed by right‐sided heart catheterization; they were prospectively included in the PH registry. All patients received PAH‐specific therapy. Computed tomography of the chest was used to confirm or exclude ILD. Results: At baseline, patients with SSc–PH‐ILD had less severe hemodynamic impairment than those with SSc‐PAH (pulmonary vascular resistance 5.7 Wood units versus 8.7 Wood units; P = 0.0005) and lower diffusing capacity for carbon monoxide (median 25% [interquartile range (IQR) 18%, 35%] versus 40% [IQR 31%, 51%]; P = 0.0005). Additionally, patients with SSc–PH‐ILD had increased mortality (8.1% at 1 year, 21.2% at 2 years, and 41.5% at 3 years) compared to those with SSc‐PAH (4.1%, 8.7%, and 21.4%, respectively; P = 0.04). Upon treatment with PAH‐targeted therapy, no improvement in the 6‐minute walk distance was observed in either group. Improvement in the World Health Organization functional class was observed less frequently in patients with SSc–ILD‐PH compared to those with SSc‐PAH (13.6% versus 33.3%; P = 0.02). Hemodynamics improved similarly in both groups. Conclusion: ILD confers a worse prognosis to SSc‐PH. Response to PAH‐specific therapy is clinically poor in SSc–PH‐ILD but was not found to be hemodynamically different from the response observed in SSc‐PAH.